Development and Application of a Plant-Based Diet Scoring System for Japanese Patients with Inflammatory Bowel Disease - Chiba, Mitsuro (Perm J, 2016)
CONTEXT: Plant-based diets (PBDs) are a healthy alternative to westernized diets. A semivegetarian diet, a PBD, has been shown to prevent a relapse in Crohn disease. However, there is no way to measure adherence to PBDs. OBJECTIVE: To develop a simple way of evaluating adherence to a PBD for Japanese patients with inflammatory bowel disease (IBD). DESIGN: PBD scores were assigned according to the frequency of consumption provided on a food-frequency questionnaire, obtained on hospitalization for 159 patients with ulcerative colitis and 70 patients with Crohn disease. Eight items considered to be preventive factors for IBD were scored positively, and 8 items considered to be IBD risk factors were scored negatively. The PBD score was calculated from the sum of plus and minus scores. Higher PBD scores indicated greater adherence to a PBD. The PBD scores were evaluated on hospitalization and 2 years after discharge for 22 patients with Crohn disease whose dietary pattern and prognosis were established. MAIN OUTCOME MEASURE: Plant-Based Diet score. RESULTS: The PBD scores differed significantly, in descending order, by dietary type: pro-Japanese diet, mixed type, and pro-westernized diet (Wilcoxon/Kruskal-Wallis test). The PBD scores in the ulcerative colitis and Crohn disease groups were 10.9 ± 9.5 and 8.2 ± 8.2, respectively. For patients with Crohn disease, those with long-term remission and normal C-reactive protein concentration were significantly more likely to have PBD scores of 25 or greater than below 25 (χ(2)). CONCLUSION: The PBD score is a valid assessment of PBD dietary adherence.